A negative electrode material of reduced graphene oxide composite zinc stannate and a preparation method and application thereof
Patent Information
- Application Number
- CN202611236463.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-30
AI Technical Summary
解决 ZnSnO3材料循环稳定性较差的问题,获得性能更为优异的负极材料
[0027]1)本发明采用溶剂热法与梯度煅烧协同作用,制备高结晶度 ZnSnO3微米颗粒。传统高温煅烧易导致颗粒团聚,而梯度煅烧通过分段控温优化晶格排列,提升结晶度与结构稳定。同时,溶剂热法在温和条件下精准控制颗粒尺寸(微米级),避免团聚问题。
Smart Images

Figure CN123017932A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of reduced graphene oxide coated zinc stannate, specifically to a negative electrode material of reduced graphene oxide composite zinc stannate, its preparation method, and its application. Background Technology
[0002] Lithium-ion button batteries are a crucial energy storage technology today. Since their inception, they have garnered widespread attention due to their excellent energy storage characteristics and have now achieved large-scale adoption and application. With the continuous iteration and upgrading of modern technology, especially breakthroughs in materials science and electrochemistry, the overall performance of lithium-ion button batteries has achieved a leap forward. The successful development of graphite anode and lithium manganese oxide cathode materials has completely broken down the technological barriers to the commercialization of lithium-ion button batteries, providing core support for their industrial application. Subsequently, with the continuous deepening of related research, new core materials such as lithium iron phosphate cathodes, ternary cathodes, and silicon-based anodes have emerged and been optimized, continuously improving the core performance indicators of lithium-ion button batteries, such as energy density, cycle life, and safety stability, laying a solid technological foundation for their comprehensive and multi-scenario popularization.
[0003] Secondly, lithium-ion button batteries, with their outstanding advantages such as being clean and pollution-free, having a long cycle life, and high energy density, have become core energy storage devices in various new energy scenarios, and are widely used in many fields such as new energy vehicles, mobile power supplies, and smart homes. Especially in the new energy vehicle industry, the large-scale application of lithium-ion button batteries is not only a core driving force for the rapid development of the new energy vehicle industry, but also demonstrates its enormous development potential and application value in the global future energy transformation process.
[0004] However, due to technological limitations, current lithium-ion button batteries still cannot meet the ever-increasing demands for performance and battery life. Therefore, researching higher-performance lithium-ion button batteries with longer battery life is imperative. In the structure of a lithium-ion button battery, the anode material is the core element determining the battery's electrochemical performance. However, the currently widely used graphite-based anode materials have a theoretical capacity of only 372 mAh / g, which is insufficient to meet the ever-increasing demands for battery performance in today's society. Therefore, developing new anode materials with superior energy storage characteristics is a key approach to improving the overall performance of lithium-ion button batteries.
[0005] In recent years, transition metal oxides have become a research hotspot for lithium-ion button battery anode materials due to their high theoretical capacity. Among them, SnO2 with a theoretical capacity of 782 mAh / g, as well as tin-based composite metal oxides such as MSnO3 and M2SnO4 (where M represents other metal elements), are considered electrode materials with great application potential due to their excellent reversibility, low lithium operating voltage, low raw material cost, simple preparation process, diverse morphologies and structures, and abundant resources. ZnSnO3, as a typical MSnO3-type material, has a theoretical capacity as high as 1317 mAh / g, which has aroused widespread research interest among researchers. However, like other tin-based metal oxides, ZnSnO3 undergoes severe volume expansion during repeated lithium-ion insertion and extraction cycles, leading to material structure collapse and separation of active material from current collector. This defect seriously impairs the cycle stability of the battery and greatly limits the practical application of this type of material. Therefore, researchers need to further optimize the preparation methods and processes of ZnSnO3 materials. Summary of the Invention
[0006] The purpose of this invention is to provide a negative electrode material composed of reduced graphene oxide and zinc stannate, along with its preparation method and applications. It utilizes a solvothermal synthesis and gradient calcination process to prepare micron-sized ZnSnO3 particles via a liquid-phase method, and then externally composites with reduced graphene oxide (RGO) to prepare a modified ZnSnO3 / RGO composite material. This addresses the problem of poor cycle stability in ZnSnO3 materials, resulting in a negative electrode material with superior performance.
[0007] In one aspect of the present invention, a method for preparing a negative electrode material of reduced graphene oxide composite zinc stannate is provided. According to an embodiment of the present invention, the method includes the following steps:
[0008] (1) Mix ZnSnO3, reduced graphene oxide and anhydrous ethanol, then transfer to a high-pressure reactor and continue the reaction in a forced-air drying oven. After the reaction is completed, cool to room temperature and collect the precipitate.
[0009] (2) The precipitate was washed and dried to obtain the negative electrode material of reduced graphene oxide composite zinc stannate.
[0010] In addition, the method for preparing a negative electrode material of reduced graphene oxide composite zinc stannate according to the above embodiments of the present invention may also have the following additional technical features:
[0011] In some embodiments of the present invention, step (1) of the method for preparing ZnSnO3 includes the following steps:
[0012] a. Dissolve SnCl4·5H2O and ZnCl2 separately, mix them, and then transfer them to a high-pressure reactor. Continue the reaction in a forced-air drying oven. After the reaction is completed, cool to room temperature, collect the precipitate, wash and dry it to obtain the ZnSnO3 precursor.
[0013] b. The ZnSnO3 precursor was placed in a muffle furnace and subjected to gradient calcination at a constant heating rate to obtain ZnSnO3.
[0014] In some embodiments of the present invention, in step a, the mass ratio of SnCl4·5H2O to ZnCl2 is (2-3):1.
[0015] In some embodiments of the present invention, in step a, the reaction temperature is 150-200°C and the time is 18-24 hours.
[0016] In some embodiments of the present invention, the parameters of the gradient calcination in step b are as follows: heating to 400°C at a heating rate of 5°C / min and calcining for 1 hour, then heating to 450°C at a heating rate of 5°C / min and calcining for 1 hour, and then continuing to heat to 500°C at a heating rate of 5°C / min and calcining for 1 hour.
[0017] In some embodiments of the present invention, step (1) of the method for preparing the reduced graphene oxide includes the following steps:
[0018] A. Under ice bath conditions, weigh out flake graphite and slowly add it to concentrated H2SO4. After magnetic stirring, weigh out potassium permanganate and slowly add it to the above mixed solution. The solution gradually turns green. Continue magnetic stirring, then transfer it to a constant temperature water bath and stir until the solution becomes a viscous, yellowish-brown mud-like precipitate. Continue stirring and slowly add deionized water to raise the temperature of the system, then stir again.
[0019] B. Add H2O2 solution to the above system to make the system turn golden yellow, then centrifuge, wash several times with dilute HCl, and then wash with deionized water until neutral;
[0020] C. Spread the precipitate obtained after centrifugation and washing evenly, freeze it, and then dry it in a vacuum freeze dryer to obtain yellow, spongy, fluffy graphene.
[0021] D. Weigh GO and add it to anhydrous ethanol, disperse it by ultrasonication, then transfer it to a reaction vessel and react it in a forced-air drying oven. After the reaction is completed, cool it to room temperature, centrifuge and dry it to obtain reduced graphene oxide powder.
[0022] In some embodiments of the present invention, in step (1), the mass ratio of ZnSnO3 to reduced graphene oxide is (0.02-0.1):1.
[0023] In some embodiments of the present invention, in step (1), the reaction temperature is 120-180°C and the time is 10-16h.
[0024] In another aspect of the present invention, the present invention provides a method for preparing the reduced graphene oxide composite zinc stannate anode material.
[0025] In another aspect, the present invention provides a lithium-ion button battery. According to an embodiment of the present invention, the reduced graphene oxide composite zinc stannate anode material is used as the anode material.
[0026] Compared with the prior art, the beneficial effects of the present invention are:
[0027] 1) This invention employs a solvothermal method combined with gradient calcination to prepare highly crystalline ZnSnO3 micron-sized particles. Traditional high-temperature calcination easily leads to particle agglomeration, while gradient calcination optimizes the lattice arrangement through segmented temperature control, improving crystallinity and structural stability. Simultaneously, the solvothermal method precisely controls particle size (micron-level) under mild conditions, avoiding agglomeration problems.
[0028] 2) High stability. GO is reduced to RGO via a solvothermal method, and then ZnSnO3 is combined with reduced graphene oxide (RGO) via a secondary solvothermal method to form a ZnSnO3 / RGO composite material. The high conductivity, good hydrophilicity, and resistance to mechanical stress of RGO are utilized to improve the structural stability of the composite material, while mitigating volume expansion and enhancing the overall conductivity of the electrode.
[0029] 3) This invention, through the external composite RGO process, prepares a ZnSnO3 / RGO composite material that maximally suppresses the volume expansion of ZnSnO3, improves cycling stability, and reduces capacity decay. Specifically, this is due to the smaller particle size of the ZnSnO3 particles embedded in the RGO, and the optimal particle size selection through the small interlayer spacing of the RGO. Micron-sized particles effectively support the shrinkage of the RGO, while the RGO also inhibits the volume expansion of ZnSnO3. Attached Figure Description
[0030] Figure 1 The XRD patterns of the reduced graphene oxide composite zinc stannate anode materials prepared in Examples 1-3 of this invention are shown below.
[0031] Figure 2 shows the Raman spectra of ZSO / RGO6 and RGO prepared in Example 2 of this invention;
[0032] Figure 3 is a scanning electron microscope image of ZSO / RGO6 prepared in Example 2 of the present invention;
[0033] Figure 4 shows the EDS test results of the ZSO / RGO6 composite material in Example 2 of the present invention, where (a) is the integrated image; (b) is the high-angle annular dark field image; (c) is the selenium image; (d) is the zinc image; (e) is the oxygen image; and (f) is the carbon image.
[0034] Figure 5 shows the application of ZSO / RGO2, ZSO / RGO6, and ZSO / RGO in Application Example 1 of the present invention. 10 Electrochemical impedance spectroscopy of the prepared battery;
[0035] Figure 6 In application example 1 of this invention, ZSO / RGO2 (a), ZSO / RGO6 (b), and ZSO / RGO are used. 10 (c) Charge-discharge curves of the prepared battery at a current density of 0.5C;
[0036] Figure 7 In Application Example 1 of this invention, ZSO / RGO2, ZSO / RGO6, and ZSO / RGO are used. 10 Rate performance diagram of the prepared battery;
[0037] Figure 8 shows the application of ZSO / RGO2, ZSO / RGO6, and ZSO / RGO in Application Example 1 of the present invention. 10 Cyclic performance of the prepared battery at current densities of 0.5C (a) and 1C (b). Detailed Implementation
[0038] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0039] Example 1
[0040] A method for preparing a negative electrode material composed of reduced graphene oxide and zinc stannate includes the following steps:
[0041] (1) Preparation of ZnSnO3 materials
[0042] a. Weigh 1.05g SnCl4·5H2O, then dissolve it in 30ml of anhydrous ethanol and label it as solution A; weigh 0.41g ZnCl2 and dissolve it in 20ml of anhydrous ethanol and label it as solution B; quickly mix solution A and solution B and stir magnetically for 20min;
[0043] b. Transfer the mixed solution to a high-pressure reactor and continue the reaction in a forced-air drying oven at a temperature of 180°C for 24 hours;
[0044] c. After the reaction is complete and cooled to room temperature, the precipitate is collected by an instrument and washed twice. The remaining precipitate is placed in a forced-air drying oven and stored at a constant temperature (80℃) for 12 hours to finally obtain the ZnSnO3 precursor.
[0045] d. The precursor is placed in a muffle furnace and subjected to gradient calcination at a constant heating rate. The calcination temperature gradient is 400℃, 450℃ and 500℃. The calcination time is as follows: heating to 400℃ at a heating rate of 5℃ / min and calcining for 1 hour, heating to 450℃ at a heating rate of 5℃ / min and calcining for 1 hour, and continuing to heat to 500℃ at a heating rate of 5℃ / min and calcining for 1 hour.
[0046] (2) Preparation of reduced graphene oxide (RGO)
[0047] a. Under ice bath conditions, weigh 2 g of flake graphite and slowly add it to a three-necked flask containing 30 ml of concentrated H2 SO4 (98%). After stirring magnetically for 30 min, weigh 8 g of potassium permanganate and slowly add it to the above mixed solution. The solution gradually turns green. Continue stirring magnetically for 2 h.
[0048] b. Transfer the system into a constant temperature water bath (35°C) and stir (12 h) until the solution becomes a viscous, yellowish-brown mud-like precipitate;
[0049] c. While continuing to stir, slowly add deionized water (6×46mL) to raise the temperature of the system, and then stir for 2 hours;
[0050] d. Add 20 ml of 30% H2O2 solution to the above system to make the system turn golden yellow;
[0051] e. Centrifuge, wash 3 times with dilute HCl (5%), and then wash 3 times with deionized water until neutral;
[0052] f. Drying: Spread the precipitate obtained after centrifugation evenly in a petri dish, seal it with plastic wrap and freeze it in a refrigerator. Then place it in a vacuum freeze dryer and dry for 24 hours to obtain yellow, spongy, fluffy GO.
[0053] The preparation of g.RGO was carried out by solvothermal method: 10 mg of GO was weighed and added to 30 ml of anhydrous ethanol, ultrasonically dispersed for 10 min, then transferred to a reaction vessel, and reacted at 120 °C for 5 h in a forced-air drying oven. After the reaction was completed, the mixture was cooled to room temperature by auto-centrifugation for 10 min to collect the precipitate, and dried at 50 °C for 12 h in a vacuum environment to obtain RGO powder.
[0054] (3) Preparation of ZnSnO3 / RGO composite material
[0055] a. Weigh 0.18 g of ZnSnO3 and dissolve it in anhydrous ethanol, label it as solution A, and the volume of solution A is 30 ml;
[0056] b. Weigh 0.02 g of RGO and dissolve it in anhydrous ethanol, label it as solution B, and make 20 ml of solution B;
[0057] c. Perform ultrasonic dispersion for 30 minutes and magnetic stirring for 30 minutes respectively;
[0058] d. Add solution B to solution A, then transfer the mixed solution to a high-pressure reactor and continue the reaction at 150°C in a forced-air drying oven for 12 h;
[0059] e. After the reaction is complete and the mixture cools to room temperature on its own, collect the precipitate using an instrument;
[0060] f. Rinse it twice;
[0061] g. Place the remaining precipitate in a forced-air drying oven and store at a constant temperature of 80℃ for 12 h to finally obtain the ZSO / RGO composite material, denoted as ZSO / RGO2.
[0062] Example 2
[0063] A method for preparing a negative electrode material of reduced graphene oxide composite zinc stannate, the only difference between this method and Example 1 is that in step (3), the amount of ZnSnO3 added is 0.19 g, the amount of RGO added is 0.01 g, and the final ZSO / RGO composite material is denoted as ZSO / RGO6. The other parameters and steps are the same as in Example 1.
[0064] Example 3
[0065] A method for preparing a negative electrode material of reduced graphene oxide composite zinc stannate differs from Example 1 only in that: in step (3), the amount of ZnSnO3 added is 0.196 g, the amount of RGO added is 0.004 g, and the final ZSO / RGO composite material is denoted as ZSO / RGO. 10 The remaining parameters and steps are the same as in Example 1.
[0066] The anode materials prepared in Examples 1-3 were subjected to morphological characterization and performance testing:
[0067] (1) X-ray photoelectron spectroscopy (XPS): such as Figure 1As shown, the three materials after RGO composite exhibit the same peak shape, indicating that their crystallinity and lattice structure are roughly the same. However, no obvious RGO crystal plane characteristic diffraction peaks were observed in the figure, which is considered to be due to insufficient RGO composite content, resulting in the RGO characteristic peaks not being well highlighted in the high-intensity peak range of ZnSnO3.
[0068] (2) Raman spectra of ZSO / RGO6 and RGO prepared in Example 2: as shown Figure 2 As shown in the figure, the RGO is clearly visible at 1330 cm. -1 and 1600 cm -1 There are two typical carbon peaks at this location, one at 1330 cm⁻¹. -1 The D-band corresponds to the structural defect strength, representing the classic disordered carbon structure, while the G-band represents the structure composed of sp... 2 The graphitization of the material is caused by in-plane vibrations of carbon atoms. The intensity ratio of the D band to the G band reflects the defects in the sample. In this case, the ID / IG ratio is much less than 1, indicating that the reduced RGO has better chemical stability. The ZSO / RGO6 spectrum shows that RGO was successfully incorporated into the sample.
[0069] (3) Scanning electron micrograph of ZSO / RGO6 prepared in Example 2. (e.g.) Figure 3 As shown, ZnSnO3 micron-sized particles were successfully composited onto RGO, forming a dense 3D structure through high-level encapsulation. This structure is beneficial for improving the material's conductivity. A large number of nanoparticles were observed on the RGO sheet surface. This is attributed to the splitting of weakly bound microspheres into nanoparticles that adhered to the RGO surface after the solvothermal reaction, which may affect the overall electrochemical stability of the material. Simultaneously, the RGO nanosheets exhibited a slight shrinkage effect, resulting in a tighter encapsulation of the ZnSnO3 particles and promoting ion and electron transport. This shrinkage is attributed to the intercalation of nanoparticles, which enhances the attractive force between RGO layers.
[0070] (4) EDS test of ZSO / RGO6 prepared in Example 2: as follows Figure 4 As shown, the elemental composition and distribution of the ZSO / RGO6 composite material clearly show that Sn, Zn, and O elements are dispersed on the C-based RGO.
[0071] Application Example 1
[0072] A method for preparing a lithium-ion button battery includes the following steps:
[0073] (1) Preparation of electrode sheets
[0074] a. Grinding: Weigh the negative electrode material of reduced graphene oxide composite zinc stannate prepared in Examples 1-3, the conductive agent (acetylene black) and the binder (polyvinylidene fluoride, PVDF) according to the mass ratio of 8:1:1, and grind them thoroughly in a mortar until a fine and uniformly dispersed composite powder is formed.
[0075] b. Slurry preparation: After the mixed materials are ground evenly, weigh an appropriate amount of N-methylpyrrolidone (NMP), add it to the mixture, and continue grinding until it presents a slurry of suitable consistency;
[0076] c. Coating: Select copper foil as the current collector, cut a single-sided copper foil sheet with a suitable length and width and a thickness of 9 μm, paste it onto a clean glass plate, and use a scraper (75 μm) to evenly coat the slurry on the rough surface of the copper foil.
[0077] d. Drying and cutting: The coated copper foil electrode sheet is placed in a vacuum drying oven and dried at 80°C for 12 hours to thoroughly remove residual solvent. After cooling to room temperature, it is removed and cut into copper foil discs with a diameter of 13 mm, which are the final prepared electrode sheets.
[0078] (2) Assembly
[0079] The operation was carried out in a vacuum glove box with water and oxygen content both below 0.1 ppm and argon atmosphere. The assembly was carried out in the following order: negative electrode shell - lithium sheet - separator - electrolyte - electrode sheet - pressing sheet - spring sheet - positive electrode shell. Then, the battery was pressed tightly with an HT-5N button battery sealing machine and tested after standing for 6 hours.
[0080] Specifically, the negative electrode material is a circular lithium metal sheet with a diameter of 15.6 mm. Considering that the insertion and extraction potential of lithium ions in the active material is higher than that of lithium metal, the lithium sheet is used as a reference electrode (which is the negative electrode for electrochemical reaction) in the system. The separator is a GF / D 1823 type glass fiber membrane with a diameter of 16 mm. The electrolyte is 1M LiPF6 dissolved in a 1:1 mass ratio of dimethyl carbonate (DMC) and ethylene carbonate (EC) mixed solution. The battery casing assembly, including the positive and negative electrode shells, spring sheets, and pressing sheets, is a CR2032 type button cell.
[0081] The prepared lithium-ion button batteries were subjected to performance testing:
[0082] (1) Electrochemical impedance spectroscopy (EIS) test: The EIS test was performed using a CHI660E electrochemical workstation manufactured by Shanghai Chenhua Instrument Co., Ltd. The frequency range of the test was set to 0.01Hz~100kHz, and the amplitude was 5mV.
[0083] like Figure 5As shown, ZSO / RGO2, ZSO / RGO6 and ZSO / RGO 10 They exhibit normal and similar Nyquist curves, and the charge transfer resistances of the three, from smallest to largest, are ZSO / RGO. 10 137.3 Ω, ZSO / RGO6 144.5 Ω, and ZSO / RGO2 202.7 Ω. This is due to the recombination of RGO, which makes Li... + The number of storage sites has increased, and the ionic / electronic conductivity has also improved.
[0084] (2) Charge and discharge test: The test was conducted using a Neware CT-3008W multi-channel electrochemical workstation manufactured by Shenzhen Neware Electronics Co., Ltd. The voltage setting range was 0.01~3 V, and the cyclic charge and discharge current density was 0.5 C and 1 C, respectively, according to the test requirements.
[0085] like Figure 6 As shown in the figure, at a current density of 0.5C, the three samples have the same charge-discharge plateau and trend, indicating that the composite RGO does not cause significant changes in the electrochemical reaction behavior of the material itself.
[0086] (3) Rate performance test: The test was conducted using a Neware CT-3008W multi-channel electrochemical workstation manufactured by Shenzhen Neware Electronics Co., Ltd. According to the test requirements, the rate test current densities were 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C, 5 C, and 0.5 C (1 C = 1317 mAh / g).
[0087] like Figure 7 As shown, ZSO / RGO6 exhibits superior rate performance, with average discharge specific capacities of 1277.3 mAh / g, 1008.6 mAh / g, 770.4 mAh / g, 667.9 mAh / g, 408.8 mAh / g, and 204.4 mAh / g at different current densities. When the current density recovers to 0.5 C, the specific capacity recovers to 745.4 mAh / g. This is because RGO inhibits particle accumulation, giving the material a stronger ability to cope with current density changes.
[0088] (4) Cyclic performance test: The CHI660E electrochemical workstation manufactured by Shanghai Chenhua Instrument Co., Ltd. was used. The voltage scan range of the CV test was 0.01 to 3.00 V, and the scan rate was set to 0.1 mV / s.
[0089] like Figure 8 As shown, ZSO / RGO2, ZSO / RGO6 and ZSO / RGO 10After a period of capacity decay, the charging and discharging process remained relatively stable. This is because the RGO sheet structure changed during the early lithium insertion / extraction process, and the volume expansion of the ZnSnO3 composite on the RGO caused the particles to fall off, which affected the stability of the material's discharge.
[0090] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the structure of the present invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
Claims
1. A method for preparing a negative electrode material of reduced graphene oxide composite zinc stannate, characterized in that, Includes the following steps: (1) Mix ZnSnO3, reduced graphene oxide and anhydrous ethanol, then transfer to a high-pressure reactor and continue the reaction in a forced-air drying oven. After the reaction is completed, cool to room temperature and collect the precipitate. (2) The precipitate was washed and dried to obtain the negative electrode material of reduced graphene oxide composite zinc stannate.
2. The method for preparing a negative electrode material of reduced graphene oxide composite zinc stannate according to claim 1, characterized in that, In step (1), the preparation method of ZnSnO3 includes the following steps: a. Dissolve SnCl4·5H2O and ZnCl2 separately, mix them, and then transfer them to a high-pressure reactor. Continue the reaction in a forced-air drying oven. After the reaction is completed, cool to room temperature, collect the precipitate, wash and dry it to obtain the ZnSnO3 precursor. b. The ZnSnO3 precursor was placed in a muffle furnace and subjected to gradient calcination at a constant heating rate to obtain ZnSnO3.
3. The method for preparing a negative electrode material of reduced graphene oxide composite zinc stannate according to claim 2, characterized in that: In step a, the mass ratio of SnCl4·5H2O to ZnCl2 is (2-3):
1.
4. The method for preparing a negative electrode material of reduced graphene oxide composite zinc stannate according to claim 2, characterized in that: In step a, the reaction temperature is 150-200℃ and the time is 18-24h.
5. The method for preparing a negative electrode material of reduced graphene oxide composite zinc stannate according to claim 2, characterized in that, In step b, the parameters for the gradient calcination are as follows: heating to 400°C at a heating rate of 5°C / min and calcining for 1 hour, then heating to 450°C at a heating rate of 5°C / min and calcining for 1 hour, and then continuing to heat to 500°C at a heating rate of 5°C / min and calcining for 1 hour.
6. The method for preparing a negative electrode material of reduced graphene oxide composite zinc stannate according to claim 1, characterized in that, In step (1), the method for preparing the reduced graphene oxide includes the following steps: A. Under ice bath conditions, weigh out flake graphite and slowly add it to concentrated H2SO4. After magnetic stirring, weigh out potassium permanganate and slowly add it to the above mixed solution. The solution gradually turns green. Continue magnetic stirring, then transfer it to a constant temperature water bath and stir until the solution becomes a viscous, yellowish-brown mud-like precipitate. Continue stirring and slowly add deionized water to raise the temperature of the system, then stir again. B. Add H2O2 solution to the above system to make the system turn golden yellow, then centrifuge, wash several times with dilute HCl, and then wash with deionized water until neutral; C. Spread the precipitate obtained after centrifugation and washing evenly, freeze it, and then dry it in a vacuum freeze-drying oven to obtain yellow, sponge-like, fluffy graphene. D. Weigh GO and add it to anhydrous ethanol, disperse it by ultrasonication, then transfer it to a reaction vessel and react it in a forced-air drying oven. After the reaction is completed, cool it to room temperature, centrifuge and dry it to obtain reduced graphene oxide powder.
7. The method for preparing a negative electrode material of reduced graphene oxide composite zinc stannate according to claim 1, characterized in that: In step (1), the mass ratio of ZnSnO3 to reduced graphene oxide is (0.02-0.1):
1.
8. The method for preparing a negative electrode material of reduced graphene oxide composite zinc stannate according to claim 1, characterized in that: In step (1), the reaction temperature is 120-180℃ and the time is 10-16h.
9. The anode material prepared by the method of any one of claims 1-8, which is a reduced graphene oxide composite zinc stannate.
10. A lithium-ion button battery, characterized in that: The anode material of reduced graphene oxide composite zinc stannate as described in claim 9 is used as the anode material.